Vernacular Structural Concepts in a Joglo House: A Case Study of Paremono Village - Suriani, Efa; Nugraheni Setyowati, Rr Diah (EMARA: Indonesian Journal of Architecture, 2025)
Research on Javanese vernacular architecture generally focuses typological and symbolic, while technical studies related to structural concepts are relatively limited, particularly in non-palace Joglo houses. This study aims to identify the vernacular structural concept of Joglo houses in Paremono Village through an analysis of geometric configurations, structural systems, and material strategies based on a single case study. The method used is a qualitative descriptive approach through measured architectural documentation, material observations, and interviews with owners and builders. The analysis was conducted comparatively, referring to the Kawruh Kalang concept and the studies of Joglo structural behavior based on literature. The results show that the Joglo structures at the study site still maintain a geometric configuration centered on the soko guru (the pilar) with consistent proportions. The structural system exhibits clear load distribution paths and flexible behavior through semi-rigid joints that allow for force redistribution. Furthermore, the use of local materials such as sengon wood and coconut trunks demonstrates a material adaptation strategy that still supports the building’s structural function. This research identifies three key conceps of vernacular Joglo structures, a centralized geometric structure, an adaptive structural system through flexible connections, and a material strategy responsive to local conditions. These findings demonstrate that vernacular structures are not only based on tradition but also embody integrated and empirically tested mechanical principles. Further research is recommended through physical and mechanical testing of materials based on the Indonesian National Standard (SNI), numerical modeling of structures, and joint reconstruction to validate structural performance more comprehensively.